Hubungan Frekuensi Pemberian ASI dengan Kejadian Hiperbilirubinemia di Ruang Neoristi - Ilma Widiya Sari (STIKES Estu Utomo, 2024)
Background: Secondhand smoke or passive smokers are people who inhale cigarette smoke from active smokers and consciously inhale cigarette smoke. The danger of inhaling cigarette smoke can increase the risk of various diseases such as heart disease, blood vessel disorders, and others. The provision of health education with videos is more interesting than conventional health education methods. Objectives: This study aims to determine the effect of health education with a video on the prevention of secondhand smoke in families. Method: This research uses quantitative research with pre experiment design, one group pre test and post test. This study used a sample of 48 respondents—bivariate analysis using Paired T-Test. Result: The results of bivariate analysis using the Paired T-Test obtained the value of Sig. (2-tailed) of 0.000 so that the p-value <0.05 it can be concluded that h0 is rejected and ha is accepted so that there is a significant difference before and after being given health education with video. Conclusion: These results indicate a significant influence on the provision of health education with video on the prevention of secondhand smoke in families in.